Aplikasi Android untuk Pencatatatan Riwayat Hasil Pemeriksaan Laboratorium secara Mandiri - Priyo Wibowo; Fransiska Ayuningtyas Widyastani; Givio Kristiana Candra (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
In today's digital era, most people use smartphones for various purposes. In the laboratory field, as an innovation in laboratory examinations, and as a form of community service to promote healthy living and change people's lifestyles, medical laboratory technicians play a role in creating medical record applications. The development of this application is based on the fact that patients often forget about the examinations they have undergone, making it difficult to accurately record medical history. The examinations conducted on patients are a benchmark for lifestyle patterns that should be carefully considered by patients. This attention begins with the periodic recording of health history, which should be done to anticipate spikes or abnormalities in the body's condition. The application system, created through a semi-automatic method for recording and reminding examinations, is able to minimize errors or inaccuracies in the examination results in the history, thus facilitating self-control of both lifestyle, examinations, and health. Medical record application software can provide health data from previous laboratory examinations and can provide reminders for the next scheduled examination.